"How Can He Be So Cruel?" Examining Issues of Trust in School Improvement Efforts. (June 2019) - Wettlaufer, Jacqueline R. A.; Sider, Steve R.
In this case, a high school vice-principal encounters tension and anger when she rewrites a staff member's report card comments without his knowledge. The case narrative examines the conflict that arises when, under time constraints and pressures to produce student reports, the vice-principal acts on a decision she believes is ethically correct only to find that she incurs a significant setback with staffing relationships largely due to wavering of trust. The analysis examines how transformational leadership builds self-efficacy in all staff founded on trusting relationships. Professional reflection provides a conduit through which educational leaders can assess their own practice and implement the changes needed to sustain school improvement planning.